Indoor air quality and sick building syndrome symptoms in administrative office at public university - Amalina Abu Mansor; Samsuri Abdullah; Aimi Nursyahirah Ahmad; Ali Najah Ahmed; Mohammad Fakhratul Ridwan Zulkifli; Suriani Mat Jusoh; Marzuki Ismail (Elsevier, 2024)
Sick Building Syndrome (SBS) is an illness among workers linked to time spent in a building. This study aimed to investigate the Indoor Air Quality (IAQ) and symptoms of Sick Building Syndrome (SBS) among administrative office workers. The IAQ parameters consist of ventilation performance indicators, and physical and chemical parameters were measured using specified instruments for three days during weekdays. The SBS symptoms were assessed by a questionnaire adopted from the Industry Code of Practice of Indoor Air Quality (ICOP-IAQ) 2010 among 19 employees from the office in East Coast Malaysia. Relationship between past symptoms and present symptoms which are draught (past symptoms) with feeling heavy headed (present symptoms) (r = 0.559, p < 0.05), room temperature too high (past symptoms) was highly correlated with feeling heavy headed (present symptoms) (r = 0.598, p < 0.01) and cough (present symptoms) (r = 0.596, p < 0.01). Room temperature (past symptoms) has a positive medium relationship with cough (present symptoms) (r = 0.477, p < 0.05) and scaling itching scalp or ears (present symptoms) has a relationship between stuffy bad air (r = 0.475, p < 0.05) and dry air (r = 0.536, p < 0.05). There was a significant association between RH with drowsiness (χ2 = 7.090, p = 0.049) and dizziness (χ2 = 7.090, p = 0.049). The association was found between temperature and SBS symptoms between temperature with headache (χ2 = 7.574, p = 0.051), feeling heavy-headed (χ2 = 8.090, p = 0.046), and skin rash itchiness (χ2 = 7.451, p = 0.044). Air movement also showed a positive association with symptoms of feeling heavy-headed (x2 = 8.726, p = 0.021). PM10 has positive significance with SBSS which are feeling heavy-headed (χ2 = 7.980, p = 0.023), and eyer's irritation (χ2 = 7.419, p = 0.038). The conclusion of this study showed that there were positive significant between temperature and relative humidity toward SBSS.